Effectiveness of exercise interventions on physical function in community-dwelling frail older people: an umbrella review of systematic reviews. (March 2018) - Jadczak, Agathe D.; Makwana, Naresh; Luscombe-Marsh, Natalie; Visvanathan, Renuka; Schultz, Timothy J.
ABSTRACT: Objectives: This umbrella review aimed to determine the effectiveness of exercise interventions, alone or in combination with other interventions, in improving physical function in community-dwelling older people identified as pre-frail or frail. Introduction: Exercise is said to have a positive impact on muscle mass and strength which improves physical function and hence is beneficial for the treatment of frailty. Several systematic reviews discuss the effects of exercise interventions on physical function parameters, such as strength, mobility, gait, balance and physical performance, and indicate that multi-component exercise, including resistance, aerobic, balance and flexibility training, appears to be the best way in which to improve physical function parameters in frail older people. However, there is still uncertainty as to which exercise characteristics (type, frequency, intensity, duration and combinations) are the most effective and sustainable over the long-term. Inclusion criteria: Participants were adults, 60 years or over, living in the community and identified as pre-frail or frail. Quantitative systematic reviews, with or without meta-analysis that examined the effectiveness of exercise interventions of any form, duration, frequency and intensity, alone or in combination with other interventions designed to alter physical function parameters in frail older people, were considered. The quantitative outcome measures were physical function, including muscular strength, gait, balance, mobility and physical performance. Methods: An iterative search strategy for ten bibliometric databases and gray literature was developed. Critical appraisal of seven systematic reviews was conducted independently by two reviewers using a standard Joanna Briggs Institute tool. Data was extracted independently by two reviewers using a standard Joanna Briggs Institute data extraction tool and summarized using a narrative synthesis approach. Results: Seven systematic reviews were included in this umbrella review, with a total of 58 relevant randomized controlled trials and 6927 participants. Five systematic reviews examined the effects of exercise only, while two systematic reviews reported on exercise in combination with a nutritional approach, including protein supplementations, as well as fruit and dairy products. The average exercise frequency was 2–3 times per week (mean 3.0 ± 1.5 times per week; range 1–7 weekly) for 10–90 minutes per session (mean of 52.0 ± 16.5 mins) and a total duration of 5–72 weeks with the majority lasting a minimum of 2.5 months (mean 22.7 ± 17.7 weeks). Multi-component exercise interventions can currently be recommended for pre-frail and frail older adults to improve muscular strength, gait speed, balance and physical performance, including resistance, aerobic, balance and flexibility tasks. Resistance training alone also appeared to be beneficial, in particular for improving muscular strength, gait speed and physical performance. Other types of exercise were not sufficiently studied and their effectiveness is yet to be established. Conclusions: Interventions for pre-frail and frail older adults should include multi-component exercises, including in particular resistance training, as well as aerobic, balance and flexibility tasks. Future research should adopt a consistent definition of frailty and investigate the effects of other types of exercise alone or in combination with nutritional interventions so that more specific recommendations can be made.